Comparative study between ultrasound guided modified pectoral nerve block versus erector spinae block in breast surgeries-prospective randomised comparative study - Shanmugam, Priadharshini; Dunna, Hemalatha; Paleti, Sophia; A. Venkateswara Rao (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Breast cancer is the most common cancer in women, comprising approximately 25% of all cases. Failure to provide effective pain control is associated with poor quality of recovery & chronic postsurgical pain after breast surgery. According to a recently published PROSPECT guideline, pectoral nerve (PECS) blocks seem to be an effective alternative to PVB for postsurgical pain management in breast surgery. In order to relieve post-operative pain in patients undergoing MRM, in this study we compared the efficacy of modified pectoral nerve block versus erector spinae plane block for breast cancer surgeries. Methods: A comparative study was conducted among 80 female patients of age 25-65 years scheduled for modified radical mastectomy surgery with ASA class I and II after obtaining approval from ethical committee. Written informed consent was obtained and research process were explained to the patients. They were randomly allocated into two groups of 40 each. Group 1: was assigned to receive 0.2% Ropivacaine 25ml for Erector spinae block and Group 2: Was assigned to receive 0.2% ropivacaine 25 ml for modified pectoral nerve block, p value <0.05 was considered statistically significant. Results: In patients receiving modified pectoral nerve block (PEC 2) there was considerably lesser opioid consumption, Ionger duration of analgesia and lesser postoperative pain score as compared to patients receiving erector spinae block (ESP) for modified radical mastectomy surgeries. Conclusions: Modified Pectoral nerve block is a potential analgesic technique in breast surgeries since it has less perioperative opioid consumption, proIonged duration of anaIgesia, Iesser postoperative pain score when compared to Erector Spinae block.